Davos man : how the billionaires devoured the world - Goodman, Peter S. (New York, NY : Custom House, 2022)
"From the New York Times's Global Economics Correspondent, a masterwork of reporting and explanatory journalism that exposes how billionaires' systematic plunder of the world has transformed 21st century life and dangerously destabilized democracy"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Billionaires; Capitalism -- Moral and ethical aspects; Wealth -- Moral and ethical aspects; Democracy